2012
DOI: 10.1111/j.1755-5949.2012.00342.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association between Parental ABO Blood Type and Autism Spectrum Disorders

Abstract: The first two authors contributed equally to this work.Autism spectrum disorders (ASDs), including autism as well as pervasive developmental disorder not otherwise specified (PDD-NOS) and Asperger's disorder, are characterized by impairments of reciprocal social interactions, problems in communication, and a restricted range of behaviors and interests [1]. Although specific causes of ASDs have yet to be found, many risk factors have been identified that may contribute to the development of ASDs. These risk fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The epigenetic alteration, confounding by genetic responsibility or social determinants of reproductive age, and mediation by age-related pregnancy risks are all probable mechanisms that could underpin these associations (Lee and McGrath, 2015). It seemed believed that ABO blood type was linked to ASDs in some way as parents' blood types are passed on to their children (Wu et al, 2012). We surveyed families with ASD to see if they have a particular ABO blood type where it has been shown that ASD mothers had 23.8% A+, 31.7% B+, 12.7% AB+, 23.8% O+ blood types while fathers had 14.3% A+, 23.8% B+, 12.7% AB+ and 20.6% O+ blood group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The epigenetic alteration, confounding by genetic responsibility or social determinants of reproductive age, and mediation by age-related pregnancy risks are all probable mechanisms that could underpin these associations (Lee and McGrath, 2015). It seemed believed that ABO blood type was linked to ASDs in some way as parents' blood types are passed on to their children (Wu et al, 2012). We surveyed families with ASD to see if they have a particular ABO blood type where it has been shown that ASD mothers had 23.8% A+, 31.7% B+, 12.7% AB+, 23.8% O+ blood types while fathers had 14.3% A+, 23.8% B+, 12.7% AB+ and 20.6% O+ blood group.…”
Section: Discussionmentioning
confidence: 99%
“…In this result, we can say that the B+ blood group of parents probably had a trend of risk for having an ASD child. In another study, It is also postulated that some unknown genetic mechanisms of a parent's blood type can contribute to the risk of autism, disrupting fetal neurodevelopment (Wu et al, 2012). However, through antibody transfer and the impact of immune markers on the developing nervous system, maternal immune-mediated conditions and autoimmune reactions can influence the risk of ASD (Kohane et al, 2012), (Zerbo et al, 2015).…”
Section: Discussionmentioning
confidence: 99%